Animal models of glucocorticoid-induced glaucoma. (December 2015) - Overby, Darryl R.; Clark, Abbot F.
Abstract: Glucocorticoid (GC) therapy is widely used to treat a variety of inflammatory diseases and conditions. While unmatched in their anti-inflammatory and immunosuppressive activities, GC therapy is often associated with the significant ocular side effect of GC-induced ocular hypertension (OHT) and iatrogenic open-angle glaucoma. Investigators have generated GC-induced OHT and glaucoma in at least 8 different species besides man. These models mimic many features of this condition in man and provide morphologic and molecular insights into the pathogenesis of GC-OHT. In addition, there are many clinical, morphological, and molecular similarities between GC-induced glaucoma and primary open-angle glaucoma (POAG), making animals models of GC-induced OHT and glaucoma attractive models in which to study specific aspects of POAG. Highlights: Clinical glucocorticoid therapy can cause ocular hypertension and iatrogenic open-angle glaucoma. Glucocorticoid-induced ocular hypertension occurs in 8 other species, from mice to nonhuman primates. Animal models of glucocorticoid-induced ocular hypertension and glaucoma are being used to better understand this important side effect of glucocorticoid therapy.